2003
DOI: 10.1046/j.1464-5491.2003.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between insulin resistance and thrombotic risk factors in high‐risk South Asian subjects

Abstract: Insulin resistance significantly clusters with fibrinolytic and coagulation factors in South Asians, which may contribute to high prevalence of vascular disease in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…SAs do indeed have a number of metabolic abnormalities, including high serum levels of apolipoprotein B, triglycerides, lipoprotein a, 7 36 37 as well as low levels of high density lipoproteins and apolipoprotein A 37. This unique lipid profile combined with higher levels of thrombotic factors of homocysteine, fibrinogen and the plasminogen activator inhibitor (PAI-1)37 along with insulin resistance38 may indicate that vascular disease risk in this ethnic group has less to do with the amount or location of the atherosclerotic plaque and more with its thrombotic tendency. In addition, C reactive protein (CRP), an inflammatory mediator, has been shown to be independently associated with cardiovascular disease even after adjustment of known confounders 39.…”
Section: Discussionmentioning
confidence: 99%
“…SAs do indeed have a number of metabolic abnormalities, including high serum levels of apolipoprotein B, triglycerides, lipoprotein a, 7 36 37 as well as low levels of high density lipoproteins and apolipoprotein A 37. This unique lipid profile combined with higher levels of thrombotic factors of homocysteine, fibrinogen and the plasminogen activator inhibitor (PAI-1)37 along with insulin resistance38 may indicate that vascular disease risk in this ethnic group has less to do with the amount or location of the atherosclerotic plaque and more with its thrombotic tendency. In addition, C reactive protein (CRP), an inflammatory mediator, has been shown to be independently associated with cardiovascular disease even after adjustment of known confounders 39.…”
Section: Discussionmentioning
confidence: 99%
“…A functional role for factor XIII in atherothrombotic disease is suggested by the finding that the Leu allele at the common Val34Leu polymorphism in the factor, XIII A-subunit gene appears to protect against myocardial infarction [159]. Factor XIII B-subunit levels correlate with features of the metabolic syndrome in both healthy south Asian subjects [160] and in the first degree relatives of subjects with type 2 diabetes [161] (two subject groups known to be at increased risk of developing both CVD and insulin resistance [95,162]). The lack of an association between insulin resistance and the A-subunit may arise because the A-subunits circulate in complex with Bsubunits, whereas B-subunits circulate in both tetrameric and free dimeric forms.…”
Section: Factor Xiii-b Subunitmentioning
confidence: 97%
“…25 In healthy subjects, PAI-1 and fibrinogen levels are elevated in South Asians compared to Europeans; and insulin resistance in South Asians is significantly clustered with prothrombotic factors such as PAI-1 and vonWillebrand Factor. 26,27 More recently, and consistent with elevations in PAI-1 in South Asians, Forouhi et al demonstrated a specific elevation in t-PA antigen, the endogenous inhibitor of PAI-1 in this ethnic group. 28 Elevations in t-PA antigen predict both diabetes 29 and CHD 30 in populations of European descent.…”
Section: Role Of Novel Risk Factorsmentioning
confidence: 68%